ANALISIS PENERAPAN PENGGUNAAN GRAPHIC EDITOR PADA PEMBUATAN OBJEK 3 DIMENSI - Retnowati, Nurcahyani Dewi (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2015)
Three-dimensional applications has evolved penetrated in almost all areas of work, especially in the field of multimedia and other virtual media. Offeature films, television, print design to production games. LightWave 3D is a software that can model an object once animate. This research model a 3D object using LightWave Modeler then analyzed the results of modeling using graphic editors in LightWave Layout. To connect between LightWave Modeler and LightWave Layout used LightWave Hub. Analysis using the graphic editor can make a better model for the selection of each layer more detail.